Mathematics teachers’ career length and teaching self-efficacy - Grigaliuniene, Monika; Lehtinen, Erno (Frontiers in Education, 2025)
The influence of teachers’ self-efficacy on the effectiveness of teaching is well-documented in educational research. The aim of this study was to investigate the construct of self-efficacy in mathematics teachers. The sample consisted of 222 Lithuanian pre-service teachers who were divided into four groups according to their length of teaching experience. Using a confirmatory factor analysis, the study identified different but highly correlated dimensions of teacher self-efficacy, in particular knowledge, recognition and (use of) methods. The results showed significant differences in general teacher self-efficacy and in the specific subscales according to career stage. Teachers at the beginning of their career or still in training (with less than 1 year of experience) generally reported lower levels of self-efficacy than more experienced groups; however, this difference was not statistically significant within the knowledge self-efficacy category. In addition, teachers with more than 30 years of experience reported lower levels of self-efficacy than teachers with 1–29 years of teaching experience.